Incidencia de la inversión en la Calidad del Gasto del presupuesto de la Universidad Nacional de San Martín. Periodo 2010-2014 - Reátegui Suxe, Muriel Arminda (2015)
The research paper entitled "Impact of Quality Investment Expenditure Budget of the National University of San Martin. Period 2010 - 2014 ", part of the problem What is the impact of investment in the quality of spending of the budget of the National University of San Martin. Period 2010 - 2014? To answer this question has been raised a null hypothesis and alternative hypothesis about non-advocacy and positive, respectively incidence. The overall purpose is precisely to explain this issue. To this effect both variables have been operationalized into dimensions and indicators allowing quantifying their causal relationship. The research is Applied and is given in the Explanatory level, not having used the experimental design of transactional type of functional relationship of cause – effect and methods; analytic - synthetic and deductive - inductive and the application of techniques such as survey and document analysis helped to develop research. Research results have led to the hypothesis H1 confirming the positive impact hypothesis allowing to reach conclusions and recommendations to improve the results of the implementation of budget investments